Gross alpha and beta activity concentrations in beers and ground water samples from selected breweries in nigeria and their potential radiological hazards - Nwodo, V.K; Luntsi, G.; Dambele, M.; Joseph, D.Z.; Abubakar, U.; Egbe, N.O.; Ogolodom, M.P.; Okeji, M.C.; Ugwuanyi, D.C.; Ezenma, I.C.; Erondu, F.O.; Ugwu, A.C.; et al. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Background: Ingestion of radionuclides via beer products may predispose consumers to radiological health hazards. This study aimed to determine the gross alpha and beta activity concentrations in beers and ground water samples in selected breweries in Nigeria and their potential radiological hazards. Materials and Methods: A cross-sectional study was conducted with some selected beer and ground water samples collected from fourteen (14) different sampled brewery locations in Nigeria. Fifteen (15) ml/L of 1 mol/dm3 of concentrated Trioxonitrate (v) acid (HNO3) was added into each keg of ground water sample immediately after collection from each brewery sites to preserve the in situ radionuclides from being adsorbed on the keg wall. No sample preparation was required for beer samples. Further sample preparation and analysis were carried out at Radiation Protection Institute, Ghana Atomic Energy Commission, Accra, Ghana (Test number: N4 and N5). Method 900 of the US Environmental Protection Agency was applied and Canberra iMaticTM Automatic low background gas-filled counter was employed to determine the mean values of Gα and β RAC in both beer and ground water samples. Results: Mean values obtained for Gα and β RAC in beer and some ground water samples were apparently safe for consumption across all breweries sites in Nigeria in line with the recommended safe limits (0.1 Bq/L for Gα RAC and 1.0 Bq/L for Gβ RAC for water) by World Health Organization (WHO). Kaduna (Kakuri) and (Kudenda) sites both in Northern Nigeria recorded the highest mean GαRAC (0.0387Bq/L) and Gβ RAC (0.0892±0.123) respectively in beer samples. Port Harcourt (Oginigba) site in southern Nigeria recorded the least mean Gα and β RAC (0.0009Bq/L and 0.0076Bq/L) in beer samples. Gα RAC in water samples from mostof the brewery sites were relatively high. Imo (Awo-omama) site recorded the highest Gα RAC (0.9330Bq/L) while Onitsha site recorded the highest value of Gβ RAC (0.694Bq/L). Port Harcourt (Oginigba) as usual maintained the least Gβ RAC (0.0064Bq/L). Conclusion: Gα and Gβ RAC from beer samples across all the breweries in Nigeria were within WHO recommendation. However, water samples across most of the brewery sites in Nigeria were higher than the WHO recommendation and therefore may potentially pose radiological health hazards (Stochastic effects) on consumers.